2015
DOI: 10.1021/jacs.5b12003
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Cobalt(III) Fluoride and Bis(perfluoroalkyl) Complexes: Catalytic Fluorination and Selective Difluorocarbene Formation

Abstract: Four perfluoroalkyl cobalt(III) fluoride complexes have been synthesized and characterized by elemental analysis, multinuclear NMR spectroscopy, X-ray crystallography, and powder X-ray diffraction. The remarkable cobalt fluoride (19)F NMR chemical shifts (-716 to -759 ppm) were studied computationally, and the contributing paramagnetic and diamagnetic factors were extracted. Additionally, the complexes were shown to be active in the catalytic fluorination of p-toluoyl chloride. Furthermore, two examples of cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 84 publications
4
56
1
3
Order By: Relevance
“…8 Baker has also shown that cationic cobalt( iii ) difluorocarbenes could undergo migratory insertion into perfluoroalkyl ligands, possibly providing a blueprint for transition metal catalyzed perfluoroolefin polymerization. 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Baker has also shown that cationic cobalt( iii ) difluorocarbenes could undergo migratory insertion into perfluoroalkyl ligands, possibly providing a blueprint for transition metal catalyzed perfluoroolefin polymerization. 9 …”
Section: Introductionmentioning
confidence: 99%
“…A catalytic variant of such a substitution was reported by Baker and co‐workers in 2015 . An acyl fluoride was generated quantitatively in the presence of CpCo(CF 3 )(F)(PPh 2 Me) as the catalyst when AgF was employed as the fluoride source.…”
Section: Formation Of Acyl Fluoridesmentioning
confidence: 88%
“…Eine katalytische Version der Substitution wurde 2015 von Baker et al. beschrieben . Hierbei wurde ein Carbonsäurefluorid quantitativ von CpCo(CF 3 )(F)(PPh 2 Me) als Katalysator mit AgF als Fluoridquelle generiert.…”
Section: Herstellung Von Carbonsäurefluoridenunclassified